Life satisfaction and mortality in elderly people: The Kangwha Cohort Study - Kimm Heejin; Sull Jae Woong; Gombojav Bayasgalan; Yi Sang-Wook; Ohrr Heechoul (BMC, 2012)
Abstract Background As well as biomedical risk factors, psychological factors have been reported to be related to mortality rate. The purpose of this study was to examine the relationship between life satisfaction and mortality in elderly people through an 11.8-year follow-up study of a prospective cohort. Methods Among 3,600 participants of the Kangwha Cohort Study who survived in 1994, 1,939 respondents of the Life Satisfaction Index (LSI)-A questionnaire were included (men, 821; women, 1118). The mortality risk for the period up to December 2005 was measured using the Cox Proportional Hazard Model. Results When the relationship between LSI and mortality was evaluated in men, the unsatisfied group with lower LSI scores showed a significantly higher risk of all-cause mortality (hazard ratio [HR], 1.42; 95% confidence interval [CI], 1.11-1.83) than the satisfied group with higher LSI scores. In women, the unsatisfied group showed a significantly higher risk of all-cause mortality (HR, 1.51; 95% CI, 1.18-1.92) and cardiovascular mortality (HR, 2.23; 95% CI, 1.30-3.85) than the satisfied group. Conclusion We found that elderly people with a lower LSI score, regardless of gender, were at risk of increased mortality from all causes, and low LSI score was also associated with cardiovascular mortality.